Profile of Patients Presenting with Asthma in Pediatric OPD of Kathmandu Medical College - Bhatta, Anwesh (Birat Journal of Health Sciences, 2018)
Introduction: Asthma is the most common chronic disorder of childhood accounting for a significant proportion of childhood disability. Although asthma has been known to be a result of complex interplay between genetic and environmental factors, other added factors have been studied. Objective: This study was conducted to assess the patient characteristics and different risk factors in children with asthma. Methodology: The study was a cross-sectional study carried out at Kathmandu Medical College for duration of six months. Patients were labeled as asthma as per the diagnosis guideline of Global Initiative for Asthma (GINA) 2016. After the diagnosis of asthma, patient and their caregivers sat for a face to face interview and a detailed proforma was filled up. Data was then entered in SPSS 20 and descriptive analysis was done to analyze the results. Results: A total of 69 patients labeled with the diagnosis of asthma were enrolled during the study period. The mean age of the enrolled patients was 6.44(±3.36) years. Male outnumbered the females (17:8). The study showed 45(65.2%) of the patients had a physician diagnosed allergic rhinitis while only around 5% had atopic dermatitis. Around 52.2% of the patients had a family history of atopy. Most of the patients (75.4%) enrolled in the study were labeled as mild persistent asthma followed by intermittent asthma in 18.8% and moderate persistent asthma in 5.8%. Conclusion: The study found asthma to be more prevalent in male population while mild persistent asthma was the most common severity present in the population. The most frequent risk factor for asthma found in the current study was physician diagnosed allergic rhinitis. BJHS 2018;3(2)6: 480-483.